Study and analysis of key generation techniques in internet of things. (17th February 2020) - Sharma, Rakesh; Jindal, Poonam; Singh, Brahmjit
Abstract: Wireless communication-based services compromised with security threats due to the open channel communication model. Free communication channel models have limited bandwidth and open port communication. Due to the limited bandwidth implementation of security channel is a very complex process in the internet of things (IoT). The trend of technology is interdisciplinary of the IoT puts the demands of secured communication. The key generation mechanism provides the end to end security communication process for the internet of things (IoT). In the process of approval and authentication used lightweight key generation methods for protection. The key generation mechanism used symmetric, asymmetric and hybrid cryptography. The process of a key generation faced a problem of high energy and time complexity. In this paper presents the study and analysis of key generation algorithms used in the internet of things (IoT). For the generation of key, four algorithms are used such as AES, 3DES, RSA and ECC. These algorithms used different key size and different file size and measured the computational cost. The measured computational cost gives the direction of key generation for wireless based device communication.